2010
DOI: 10.1007/s11120-010-9532-1
|View full text |Cite
|
Sign up to set email alerts
|

The “green” phylogenetic clade of Rieske/cytb complexes

Abstract: More than a decade ago, Heliobacteria were recognised to contain a Rieske/cytb complex in which the cytochrome b subunit is split into two separate proteins, a peculiar feature characteristic of the cyanobacterial and plastidic b (6) f complex. The common presence of RCI-type reaction centres further emphasise possible evolutionary links between Heliobacteria, Chlorobiaceae and Cyanobacteria. In this contribution, we further explore the evolutionary relationships among these three phototrophic lineages by both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…The Rieske/cytb complexes are energyconverting enzymes that operate between the initial electron donors and the terminal electron acceptors of respiratory chains. In halophiles, two distinct clusters of Rieske/cytb encoding genes have been described, (i) the Rieske/cytb complex cluster along with the NAR-encoding genes implied in the denitrifying chain (Martinez-Espinosa et al, 2007) and (ii) the Rieske/cytb complex cluster with a gene coding for an halocyanin followed by a cytochrome b (Nitschke et al, 2010). The implication of this second type of gene cluster in aerobic respiration seems the most likely function, where the halocyanin will work as an electron acceptor of the Rieske/ cytb complex and the donor to a cytochrome oxidase (Baymann et al, 2012).…”
Section: Inferred Metabolic and Ecological Featuresmentioning
confidence: 99%
“…The Rieske/cytb complexes are energyconverting enzymes that operate between the initial electron donors and the terminal electron acceptors of respiratory chains. In halophiles, two distinct clusters of Rieske/cytb encoding genes have been described, (i) the Rieske/cytb complex cluster along with the NAR-encoding genes implied in the denitrifying chain (Martinez-Espinosa et al, 2007) and (ii) the Rieske/cytb complex cluster with a gene coding for an halocyanin followed by a cytochrome b (Nitschke et al, 2010). The implication of this second type of gene cluster in aerobic respiration seems the most likely function, where the halocyanin will work as an electron acceptor of the Rieske/ cytb complex and the donor to a cytochrome oxidase (Baymann et al, 2012).…”
Section: Inferred Metabolic and Ecological Featuresmentioning
confidence: 99%
“…It has recently been found that this space in the b 6 f complex can largely be filled by a lipid and the bound chlorophyll a [25] (figure 3). The eight versus seven TMH problem in the cyt b polypeptide in energy-transducing membranes has previously been discussed in the evolutionary context of the residence of the split (four þ three) seven TMHs of b 6 f-like complexes in the 'green clade' [38]. In addition to the questions posed in [38] in the context of the finding that a lipid molecule in the b 6 f complex occupies much of the space filled by the eighth TMH in the bc 1 complex, one may ask: (i) which cyt bc complex appeared first in evolution, the respiratory or photosynthetic cyt bc complex?…”
Section: Discussionmentioning
confidence: 99%
“…More recently, with expanded genome sampling, a grouping of the b-type cytochromes from cyanobacteria, chlorobi and heliobacteria was suggested, all of which share RCI-type photosystems (Nitschke et al, 2010).…”
Section: Schutz Et Al Reviewed the Evolution Of Cytochrome Bc Complexmentioning
confidence: 99%
“…Previous analyses (Schutz et al, 2000, Lebrun et al, 2006, Nitschke et al, 2010, Dibrova et al, 2013 have attempted to derive a complete phylogeny of cytochrome-b from a diverse set of prokaryotes, but they mostly focus on the comparison of cytochrome b 6 of the b 6 f complex of photosynthesis and the cytochrome bc complex of respiration. Also, in those analyses only some cytochromeb domain containing proteins were included while some other were excluded; this might skew the results, and thus the conclusions.…”
Section: Schutz Et Al Reviewed the Evolution Of Cytochrome Bc Complexmentioning
confidence: 99%
See 1 more Smart Citation